Characterization of extracellular proteases from Pseudomonas sp. 16D4 and Dermacoccus sp. 17D6 isolated from arctic regions [electronic resource] - Liew, Kok Jun, 1991-, author (2015)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2015